2019
DOI: 10.1080/14606925.2019.1595407
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the double-gap in circularity. Addressing the intention-behaviour disparity in fashion

Abstract: The contemporary fashion industry is a broken system in need of reform, moving away from a dated linear model to adopt principles reflective of modern societal challenges. Through initial explorative studies and a thorough literature search, a fundamental engagement gap with principles of circularity has been identified, which continues to challenge the application of sustainable innovation methods. This paper focuses on the role design can play in the application of a circular model through product-life exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…One example from the tourism sector, in which the process of co-creation facilitated the sharing of resources in the integration of physical and digital worlds and as such, enriched the tourism experience of clients (Pencarelli, 2020). Consumer awareness of CE: studies have indicated that the collaboration and co-creation approach involving consumers has raised awareness of the practices of CE for those involved (James et al , 2019; Schroder et al , 2019). One reason for this is that the co-creation approach and participative design facilitate the interaction and communication between companies and consumers, increasing awareness of the importance of sustainable consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example from the tourism sector, in which the process of co-creation facilitated the sharing of resources in the integration of physical and digital worlds and as such, enriched the tourism experience of clients (Pencarelli, 2020). Consumer awareness of CE: studies have indicated that the collaboration and co-creation approach involving consumers has raised awareness of the practices of CE for those involved (James et al , 2019; Schroder et al , 2019). One reason for this is that the co-creation approach and participative design facilitate the interaction and communication between companies and consumers, increasing awareness of the importance of sustainable consumption.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is that the co-creation approach and participative design facilitate the interaction and communication between companies and consumers, increasing awareness of the importance of sustainable consumption. The interaction of companies with consumers may empower the sense of responsibility consumers share, as well as allowing the joint development of future scenarios and environmentally sustainable product lifecycle planning (James et al , 2019). Schroder et al (2019) also highlight that the co-creation processes developed together with nontraditional interested parties, such as citizen groups and representatives of the informal sector, may promote more sustainable lifestyles in cities.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these two factors, triggers related to, for example, appearance, time, or previous care experiences are needed to enact consumers to care for their products. Similarly, numerous authors examined how a closer understanding of the attitudes and perspectives of end-users as it pertains to ownership, disposal, and reuse of objects, and the key mechanisms behind caring for one's possessions (e.g., affection, responsibility, and commitment) can greatly help extend the lifespan of products [66,67,69,97]. While assessing six German hospitals and their recycling performances, Vogt and Nunes [98] analyzed some motivational factors for environmental behavior.…”
Section: Design For Circular Consumptionmentioning
confidence: 99%
“…Contributions mostly circle around two aspects. First, it is critical to have a clear understanding of consumers' routines, rituals, and motivational aspects of using, maintaining, repairing, disposing, and recycling products (e.g., [95]); such understanding can help in the design of longer-lasting products and support the implementation of the circular economy (e.g., [67,97]). Second, visual and communication design-for example, applied to flyers, product labels, and websites that present key characteristics of products and services and the way in which they leverage circular economy processes-can greatly help to educate consumers (e.g., [99,100]).…”
Section: Contribution Of Industrial Design Research To Circular Economentioning
confidence: 99%
See 1 more Smart Citation